بيع العقارات المملوكة على الشيوع في القانون المدني الجزائري - معمر، فرقاق Muammar, Ferqaq; سفيان، فلاح Sufian, Falah (جامعة حسيبة بن بوعلي بالشلف, 2019)
الشيوع حالة قانونية تنجم عن تعدد أصحاب الحق العيني، ولعل أهم أسبابها في الجزائر هو الميراث، وقد تناولها المشرع الجزائري بالتفصيل في المواد 714 وما يليها من القانون المدني الجزائري، وخصها بأحكام أخرى في نصوص قانونية متفرقة، والمال المملوك على الشيوع تثور بشأنه عدة إشكالات فيما يتعلق بمزاولة كل مالك لسلطة الاستعمال والاستغلال والتصرف باعتبارها أركان الملكية، وما يهمنا في هذا المقام هو بيع المشاع باعتباره تصرفا من التصرفات القانونية، وهو الوسيلة الغالبة التي يخرج بمقتضاها المالك على الشيوع من هذه الحالة دون حاجة إلى إنهائها، وهذا ما دفعنا أكثر للكتابة في هذا المضوع دون غيره.
The Common Law case is the result of the multiplicity of right holders in kind, and perhaps the most important reasons in Algeria is the inheritance, and dealt with the Algerian legislator in detail in articles 714 and the following of the Algerian Civil Code, and singled out other provisions in separate legal texts, and money is common in which several problems arise With regard to the exercise of each owner of the authority to use, exploitation and disposal as the cornerstones of property, and what concerns us here is the sale of the public as a behavior of legal actions, which is the predominant means by which the owner of the common of this case without the need to end, T to write in this Alamadua without the other.
Keywords: الجزائر -- القانون المدني -- بيع العقارات -- البيع على الشيوع -- نقل الملكية